(untitled) (New Agenda: SA Journal of Social and Economic Policy, 2025)
The incoherent trade policy of the United States moved into uncharted territory in April with the announcement of illogical and destructive tariffs that sent shock waves across the global trading systems. Africa, with the rest of the world, will be profoundly harmed. African countries have often been victims of the globalised economic order, and in ways that make them even more vulnerable to its disruption. Chaotic and unpredictable tariff ‘pauses’, intensifications and exemptions have been announced week after week, further unsettling an already unstable economic and geo-political environment.